Information systems and technology education from the university to the workplace - Lowry, Glenn R.; Turner, Rodney L. (Gale virtual reference library, 2007)
Presents a multifaceted, global view of the human dynamics of education, supply, demand, and career development in the information systems and technology industry. Provides a tool to meet the challenges of providing improved education and employing an optimal supply of information systems and technology graduates in the decades to come.